Update in the Use of Ketamine for Anesthetists: An Evidence-Based Review - Akaravinek, Piraya (Thai Journal of Anesthesiology, 2021)
Ketamine has been mainly used as an anesthetic. It contains a unique property that it stimulates several receptors combining with the analgesic property, which is distinct to other anesthetics, and it does not suppress the cardiovascular system. However, it is limited in that it consists of a psychological side effect. Ketamine has been widely used for anxiolytic premedication in children. It has been reported that ketamine provides superior efficacy comparing to other anesthetics or placebo. Moreover, ketamine can be used in the outpatient setting without significant adverse outcomes. In trauma, there is a lack of evidence showing the superiority of ketamine to other drugs in terms of mortality or hospital stay. Ketamine has been shown to decrease postoperative shivering. It is potent analgesia in both acute and chronic phases. It can also be used as an alternative drug to control seizure when the standard medication is not effective.